Trade Policies and Export growth - employment and poverty impact in Tanzania - Jörgen Levin; Mikael Olin (Örebro University School of Business, 2008)
This report focuses on trade and exchange rate policies in Tanzania. The composition of Tanzanian exports has changed dramatically since early 2000. In examining the determinants of trade with a particular focus on Tanzanian exports, we found that changes in the real exchange rate did not have a significant impact on exports. However, supply-side effects and trading partner economic performance are more important, as is the distance to market (or transport cost). The second part of this report discusses the impact of trade reforms on employment and poverty in the Tanzanian economy. In the long-term scenarios poorer households seem to gain more from trade liberalisation compared to the richer household groups. In the short-term, trade liberalisation would be beneficial to female workers and poor households, if labour is able to move between sectors. If wages are rigid, trade liberalisation will lead to unemployment and wages for casual labour will drop significantly. A nominal wage increase during liberalisation can have a significant impact on unemployment, driving casual workers' wages down further. If the trade union adjusts worker premiums during trade reform, this would not only save some of the jobs of members, but also benefit non-unionised workers in other sectors as well. The alternative option of a reduction in export taxes would have a stronger impact on export supply, poor households would gain more than with liberalisation..
Keywords: C68; F01; F16; 330; Trade liberalisation; labour markets; poverty; Tanzania